EBV BART MicroRNAs Target Multiple Pro-apoptotic Cellular Genes to Promote Epithelial Cell Survival. - Dong Kang (PLoS Pathogens, 2015)
Epstein-Barr virus (EBV) is a ubiquitous human γ-herpesvirus that can give rise to cancers of both B-cell and epithelial cell origin. In EBV-induced cancers of epithelial origin, including nasopharyngeal carcinomas (NPCs) and gastric carcinomas, the latent EBV genome expresses very high levels of a cluster of 22 viral pre-miRNAs, called the miR-BARTs, and these have previously been shown to confer a degree of resistance to pro-apoptotic drugs. Here, we present an analysis of the ability of individual miR-BART pre-miRNAs to confer an anti-apoptotic phenotype and report that five of the 22 miR-BARTs demonstrate this ability. We next used photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) to globally identify the mRNA targets bound by these miR-BARTs in latently infected epithelial cells. This led to the identification of ten mRNAs encoding pro-apoptotic mRNA targets, all of which could be confirmed as valid targets for the five anti-apoptotic miR-BARTs by indicator assays and by demonstrating that ectopic expression of physiological levels of the relevant miR-BART in the epithelial cell line AGS resulted in a significant repression of the target mRNA as well as the encoded protein product. Using RNA interference, we further demonstrated that knockdown of at least seven of these cellular miR-BART target transcripts phenocopies the anti-apoptotic activity seen upon expression of the relevant EBV miR-BART miRNA. Together, these observations validate previously published reports arguing that the miR-BARTs can exert an anti-apoptotic effect in EBV-infected epithelial cells and provide a mechanistic explanation for this activity. Moreover, these results identify and validate a substantial number of novel mRNA targets for the anti-apoptotic miR-BARTs.